Wykorzystanie źródeł administracyjnych w szacowaniu informacji o działalności gospodarczej małych przedsiębiorstw w przekroju sekcji PKD i województw - Gołata, Elżbieta (Use of administrative data sources in estimation of small business information in the joint cross-section of Polish classification of economic activities and regions, 2006)
The study was aimed at taking into account and applying tax data for a more effective use of a conducted by Central Statistical Office survey sampling of small businesses (employing up to 9 people which is called SP-3). The objective was understood in twofold manner. First, it was verification of the hypothesis concerning the possibility of improving estimation precision in scope available to date. Secondly, it was intended as a possible extension of estimation scope for joint distribution by regions (voivodship) and economic activity division (PKD). The set of basic economic information, for the aim of this study, was limited to employment, revenues, costs and wages. The following problems are discussed: characteristics of data sources about economic activity of small business enterprises, evaluation of possibilities to integrate available data sources and their usefulness in satisfying the demand for economic information about small business by regions and PKD division, statistical description and characteristics of the distribution of variables estimated, evaluation of direct estimation precision when applied to domains defined as PKD division by regions, an attempt to apply tax data and SP3 survey to indirect estimation of small business characteristics for PKD sections by regions (use of use synthetic ratio estimation). Results obtained in the study entitle to draw the following conclusion. The approach involving de-aggregating direct estimates for lower level domains is characterised by great simplicity yet synthetic estimations can be heavily biased due to incompleteness of the tax register as an auxiliary data source. Application of indirect estimation to small business data requires special consideration of the heterogeneity of the distribution of economic variables. It is also extremely important for future estimations that public statistics are granted access to complete tax registers. This would, hopefully, enable analysts to make significant improvements in the estimation precision and reduce the degree of error.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1142, s. 109-126